Stacking Ensemble-Based Machine Learning Model for Predicting Deterioration Components of Steel W-Section Beams - A. Khoshkroodi; H. Parvini Sani; M. Aajami (Buildings, 2024)
The collapse evaluation of the structural systems under seismic loading necessitates identifying and quantifying deterioration components (DCs). In the case of steel w-section beams (SWSB), three distinct types of DCs have been derived. These deterioration components for steel beams comprise the following: pre-capping plastic rotation (θp), post-capping plastic rotation (θpc), and cumulative rotation capacity (Λ). The primary objective of this research is to employ a machine learning (ML) model for accurate determination of these deterioration components. The stacking model is a powerful combination of meta-learners, which is used for better learning and performance of base learners. The base learners consist of AdaBoost, Random Forest (RF), and XGBoost. Among various machine learning algorithms, the stacking model exhibited superior functioning. The evaluation metrics of the stacking model were as follows: R2 = 0.9 and RMSE = 0.003 for θp, R2 = 0.97 and RMSE = 0.012 for θpc, and R2 = 0.98 and RMSE = 0.09 for Λ. The significance of input variables, specifically the web-depth-over-web-thickness ratio (h/tw) and the flange width-to-thickness ratio (bf/2tf), in determining the deterioration components was assessed using the Shapley Additive Explanations model. These parameters emerged as the most crucial factors in the evaluation.